The Dynamics of Product and Labor Market Power: Evidence from Lithuania - Ziran Ding; Jose Garcia-Louzao; Valentin Jouvanceau (Center for Economic Studies and ifo Institute (CESifo), 2024)
This paper characterizes the power dynamics of firms in both product and labor markets in Lithuania between 2004 and 2018. We first show that both markets are not perfectly competitive, as both price markups and wage markdowns are far from unitary and homogeneous. Interestingly, we unveil that the dynamics of these margins followed different patterns. On the one hand, both the dispersion and the economy-wide markup have increased, indicative of an increase in product market power. On the other hand, we document a decline in monopsony power, as both the heterogeneity and the aggregate level of markdowns have declined. Altogether, our results underline the importance of jointly analyzing product and labor markets when assessing firms' market power.
Keywords: D40; E20; J30; L10; 330; firm heterogeneity; monopoly; markups; monopsony; markdowns